APLIKASI INFORMASI WISATA DI KOTA MALANG BERBASIS ANDROID - Meike Wijiati; Lukman Affandi; Evy Sophia (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2025)
Malang have lots of interesting sights to visit. This could be utilized to introduce a wider variety of tourist sites in the city of Malang, such as historic sites, restaurants and hotels, so that the visitors more aware the location of tourism and supporting facilities such as hotels and restaurants. Tourism information is merely of information in writing obtained website. Society does not save time and a rather complex in search of the information. The purpose of research to build application smartphone android to ease users in get information tourist destinations in Malang. The research variables historic tourism, hotels, and restaurants that are unfortunate. The method used in this study refers to the waterfall systems research methods: analysis, designing, coding and testing. System development method used is the System Development Life Cycle (SDLC). The result of this research provide facilities user and save time in searching for tourism in malang compared to seek for information tourism one by one tourism information on the website .